Mudanças históricas e epistemológicas na taxonomia e suas repercussões atuais no ensino de ciências e biologia - Klepka, Verônica (2017)
The Sciences and Biology Teaching has as one of its objectives to broaden the understanding that subjects has of the biological organization existing in their own body as well as in the environment of which they are part. In this sense, the classification content of living beings is the basis upon which all other disciplines of biology work. Despite this, the classifications are underestimated and little studied. Historically, many changes have occurred in the way of biological classification. Since the ancient Greeks, different ways of classifying life were developed. The evolution caused one of the most significant changes observed in the classification process and in the Biological Sciences as a whole. Recently, the Systematic Phylogenetic was proposed as a classification methodology being considered by some authors as one of the revolutions in Biology. However, this supposed revolution did not break with previous methodological paradigm, the Linnaean classification. In this sense, this research aimed to investigate how the epistemological changes contained in the History of Biological Classification affect the pedagogical practice of Science and Biology teachers. From this, the objective was to analyze in the pedagogical practice of science and biology teachers the reflection of the epistemological changes existing in the historical and methodological context of the biological classification. The qualitative research was carried out in two steps: i) through structured questionnaire composed of eight questions that dealt with the teaching of classification and the History and Nature of Classificatory Science applied to teachers / researchers of Higher Education; and ii) through a Continuing Education Course offered to teachers of Basic Education in the city of Uberaba-MG, which had three moments of data collection: a focus group session; interactions and perceptions arising from the activities of the course; and a class proposal, all of them having as their central axis the biological classification. The course was recorded in audio and the speeches, together with the answers of the higher education teachers to the questionnaire, were transcribed and submitted to the Categorical Analysis methodology. As results, we observe that the historical and epistemological changes occurred in the biological classification are recognized by professors and researchers of Higher Education who consider that there have been no revolutions or ruptures, as part of the literature of the area. However, there is no consensus on how classification should be taught. The continued formation provided although it has promoted the appropriation of theoretical and methodological aspects of Phylogenetic Systematics did not guarantee the use of this knowledge in real teaching situations. This fact demonstrates that historically constructed knowledge about biological classification needs to be part of teacher formation, through a process that enables dialogue with different areas of knowledge, with evolution as an interpretative axis.